'It's all in Plato': Platonism, Cambridge Platonism, and C.S. Lewis. (April 2021) - Bryson, James
Abstract : In 1924 C.S. Lewis began work on a doctoral dissertation, the subject of which was to be the Cambridge Platonist Henry More (1614–1687). A number of scholars gloss this important moment in Lewis's intellectual and spiritual journey, and some offer penetrating, if cursory, analysis of how Lewis's close reading of More would have helped to shape the young scholar's philosophical and theological imagination. These important contributions notwithstanding, the influence of More and, by extension, the Platonic tradition longue durée are not properly understood in Lewis scholarship. This article argues that Cambridge Platonism and Henry More in particular were a crucial part of Lewis's initiation into, and appropriation of, the Platonic tradition. The tradition of Platonism to which the Cambridge Platonists introduced Lewis shaped the way he thought about a number of topics central to his own moral, philosophical, and religious outlook, including the relationship between the moral and the numinous, and imagination and reality, but also pneumatology, angelology, and his understanding of the supernatural, miracles, prophetic wisdom, and, especially, the nature of love.